2D stationary computational printing of cement-based pastes. (September 2022) - Mohammad, Abdul Salam; Biernacki, Joseph J.
Abstract: An efficient computational strategy has been developed for modeling additively manufactured cement-based materials which captures the dynamics of 2D slices at a stationary location along a print path, i.e. 2-D stationary computation printing (2D-SCP). Flow rheometry was used to experimentally establish the fluid properties of cement pastes of various water contents and to calibrate the computational model. The model was validated using mini conical slump flow tests. A hollow cylinder geometry was used as a benchmark for printed objects. Deformations and rates of deformation for the free-surface flow were then simulated for like 2-D geometries. The relative importance of yield stress and structuration rates were quantified by comparing the 2D-SCP model outcomes with cut cross-sections of the 3D printed cylinders. Good agreement between printed objects and model outcomes were found in all cases. Quantification of print fidelity shows that 2D-SCP is a strong predictor of actual printed object outcomes.